Efforts To Improve Fine Motor Skills In Children Through Color Paper Folding Activities In Group A Of Dharma Wanita Seba Kindergarten - Marselina Ga; Siti Aminah Machmud (Early Childhood Education Development and Studies (ECEDS), 2022)
Who researched the problem effort to improve the fine motor skills of children through paper folding color? the purpose of research is to know children's developing fine motor skills through paper folding color. This research is a classroom action research conducted in two cycles. The place this research is TK (kindergarten) Dharma Wanita (ladies) Seba. The research time is from March to May 2023. Collection techniques sheet format observatory and performance. That has been collected is analyzed by qualitative descriptive technique through the calculation of the presentation. The result of this class action is the first cycle of the fine motor skills of children in group B TK (kindergarten) Dharma Wanita (ladies) Seba to achieve 63,3 %. In the second cycle after applying the color paper media reached 90,9 %. This means there has been an increase in children's fine motor skills in group B TK (kindergarten) Dharma Wanita (ladies) Seba by 27,3 %. Based on the results of research and data analysis can be concluded that the application of the color paper media can improve the motor skills of children in group B TK Dharma Wanita Seba. Keywords: Fine Motor, Color Paper Folding